The Painted Veil - Akhmadullina Alina Ildarovna (Euro Asian Journal Publishing, 2024)
This article explores the integration of philosophical concepts into language teaching as a means to enhance linguistic proficiency and critical thinking skills among learners. By incorporating philosophical discussions, educators can create an engaging and reflective classroom environment that promotes not only language acquisition but also deeper understanding of cultural and ethical perspectives. The benefits of this interdisciplinary approach include improved critical analysis, enhanced cognitive flexibility, and a greater appreciation for diverse viewpoints. Through practical methods such as Socratic seminars, reflective writing, and analysis of philosophical texts, language teachers can cultivate a more holistic educational experience that prepares students for both academic success and personal growth.
Keywords: Language Teaching; Philosophy in Education; Critical Thinking